Impact on neurosurgical management in Level 1 trauma centers during COVID-19 shelter-in-place restrictions: The Santa Clara County experience. (June 2021) - Zhang, Michael; Zhou, James; Dirlikov, Ben; Cage, Tene; Lee, Marco; Singh, Harminder
Highlights: For study sites, early quarantine saw a decrease in total TBI and spinal fractures. Number of neurosurgery trauma consults, but not procedures or admissions decreased. Rate of neurosurgery consults among traumas did not change during quarantine. ED and hospital dispositions for neurosurgery traumas did not change. Volume and disposition did not differ between neighboring Level 1 trauma centers. Abstract: Early COVID-19-targeted legislations reduced public activity and elective surgery such that local neurosurgical care greatly focused on emergent needs. This study examines neurosurgical trauma patients' dispositions through two neighboring trauma centers to inform resource allocation. We conducted a retrospective review of the trauma registries for two Level 1 Trauma Centers in Santa Clara County, one academic and one community center, between February 1st and April 15th, 2018–2020. Events before a quarantine, implemented on March 16th, 2020, and events from 2018 to 19 were used for reference. Encounters were characterized by injuries, services, procedures, and disposition. Categorical variables were analyzed by the χ2 test, proportions of variables by z-score test, and non-parametric variables by Fisher's exact test. A total of 1, 336 traumas were identified, with 31% from the academic center and 69% from the community center. During the post-policy period, relative to matching periods in years prior, there was a decrease in number of TBI and spinal fractures (24% versus 41%, p < 0.001) and neurosurgical consults (27% versus 39%, p < 0.003), but not in number of neurosurgical admissions or procedures. There were no changes in frequency of neurosurgery consults among total traumas, patients triaged to critical care services, or patients discharged to temporary rehabilitation services. Neurosurgical services were similarly rendered between the academic and community hospitals. This study describes neurosurgical trauma management in a suburban healthcare network immediately following restrictive quarantine during a moderate COVID-19 outbreak. Our data shows that neurosurgery remains a resource-intensive subspeciality, even during restrictive periods when overall trauma volume is decreased.